Khotbah Ekspositori sebagai Sarana Pertumbuhan Iman Jemaat - Dewi Magdalena Rotua; Ridwan Henry Simamora; Julisno Torokowesi; Teofilus Kevin Irawan; Oktavianus Stanly Betosi (Sekolah Tinggi Teologi Sriwijaya, 2026)
Expository preaching is a form of ministry of the Word that interprets and communicates the meaning of biblical texts systematically, historically, and contextually, thereby addressing the spiritual needs of the congregation. Although expository preaching has been widely discussed in homiletical studies, existing research has generally focused on delivery techniques or principles of interpretation, while its theological construction as an instrument for fostering the congregation’s growth in faith remains underdeveloped. Therefore, this study aims to reconstruct the role of expository preaching as a model of faith formation that integrates hermeneutical, theological, and transformative dimensions. This study employs a descriptive qualitative method through a literature review of relevant sources in biblical theology, homiletics, and spiritual growth. The findings indicate that expository preaching preserves the doctrinal integrity of the church, cultivates congregations that are critical and mature in faith, strengthens the spiritual life of the church, and addresses congregational needs. The novelty of this study lies in its conceptual formulation of expository preaching as an integrative model that connects biblical interpretation, spiritual formation, and the continuous development of faith. Thus, expository preaching should be understood not merely as a preaching method but as a strategy for congregational formation that produces maturity in faith rooted in biblical truth and responsive to the challenges facing the contemporary church.